Capital structure and value of reported earnings: evidence from an emerging market. Issue 10 (7th June 2017) - Farooq, Omar; Asgarov, Ziya; Guliyev, Ayaz; Islam, Toghrul; Kalinina, Yuliya; Pashayev, Zakir
ABSTRACT: This article documents a nonlinear impact of capital structure on the value of reported earnings in India during the period between 2009 and 2015. Our results show that earnings reported by firms with moderate level of debt are more valuable than earnings reported by firms with low or high level of debt. Our results are robust across various proxies of capital structure and across various sub-samples. This article argues that moderate level of debt is associated with low-agency problems, while low and high level of debt is synonymous to high-agency problems. Differences in agency problems result in reported earnings that have very different levels of relevance.